Review of Powell, Anton and Andrew Burnett (eds.). 2020. Coins of the Roman Revolution, 49 BC-AD 14. Evidence without Hindsight: Swansea: Classical Press of Wales. Pp. xviii+238, ills. ISBN 978-1-910589-76-2. £60. - Campana, Alberto (KOINON: The International Journal of Classical Numismatic Studies, 2022)
This volume originated as a panel at the Ninth Celtic Conference in Classics at University College Dublin, 22-25 June 2016. The panel was conceived by Anton Powel, with advice from Dr Kathryn Welch. It attracted seventeen papers, eleven of which are represented here. Andrew Burnett attended the panel and agreed to edit the planned volume and to write its Introduction, after news of the death of Anton Powell (1947-2020), who was an important scholar of the history and historiography of ancient Greece and Rome.